DAMPAK PEMBELAJARAN ONLINE DI MASA PANDEMI COVID-19 - Enny Irawati (STT BIBLIKA JAKARTA, 2022)
The Covid-19 virus is a frightening specter because there is a high death rate and transmission is so fast. And online-based education is one of the methods used today to reduce the rate of transmission of COVID-19. This study is intended to provide an explanation of the effectiveness of online education in suppressing the spread of COVID-19. This study uses qualitative research methods, using literature studies. The results of the study show that online learning is effective in suppressing the spread of covid-19, but there are still positive and negative impacts from the online learning system. Therefore, students and educators must be able to work together with creative packaging so that the quality of education is not reduced even though it is held online.